2015
DOI: 10.1016/j.ceca.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine activates calcium channels through dopamine transporter-mediated depolarization

Abstract: Amphetamine (AMPH) and its more potent enantiomer S(+)AMPH are psychostimulants used therapeutically to treat attention deficit hyperactivity disorder and have significant abuse liability. AMPH is a dopamine transporter (DAT) substrate that inhibits dopamine (DA) uptake and is implicated in DA release. Furthermore, AMPH activates ionic currents through DAT that modify cell excitability presumably by modulating voltage-gated channel activity. Indeed, several studies suggest that monoamine transporter-induced de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…2123 In our calcium fluorescence assay, substrate-induced transporter-mediated currents are coupled to voltage-gated Ca 2+ channels which causes opening of calcium channels increasing the intracellular Ca 2+ concentration. 15,24,25 As we have described before 15 and as shown here, cells expressing these two proteins and loaded with a cytosolic Ca 2+ sensor constitute a biosensor that produces a detectable Ca 2+ signal in response to transporter-mediated currents induced by substrates (Figure. S3A).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…2123 In our calcium fluorescence assay, substrate-induced transporter-mediated currents are coupled to voltage-gated Ca 2+ channels which causes opening of calcium channels increasing the intracellular Ca 2+ concentration. 15,24,25 As we have described before 15 and as shown here, cells expressing these two proteins and loaded with a cytosolic Ca 2+ sensor constitute a biosensor that produces a detectable Ca 2+ signal in response to transporter-mediated currents induced by substrates (Figure. S3A).…”
Section: Resultsmentioning
confidence: 68%
“…To improve the dynamic range of these recordings the experiments where repeated using a different Ca 2+ channel, Ca V 1.3, that has a lower threshold of activation and requires less depolarization to open. 25 When Ca V 1.3 rather than Ca V 1.2 was used, the efficacy of 4 S and 4 R to induce Ca 2+ signals increased to 88% and 68%, respectively. The improvement of the signal, when Ca V 1.3 was used, suggests that 4 S and 4 R act as partially efficacious substrates to evoke modest inward current at NET.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The actions of AMPH to elevate Ca 2+ levels were blocked by desipramine, suggesting that AMPH-induced depolarization may be responsible for Ca 2+ channel activation. Consistent with this idea, Cameron et al (2015) recently reported an ability of AMPH to activate VGCCs via transporter-mediated depolarization. Although these studies were of DAT expressing cells, NET is also electrogenic and generates significant currents in response to substrate interactions (Galli et al, 1998).…”
Section: B Regulation Of Norepinephrine Transporter Bymentioning
confidence: 60%
“…These potentially depolarizing transporter-mediated substrate-induced sodium currents (Sonders et al, 1997;Sitte et al, 1998) cause reverse transport or release of neurotransmitter. The exogenous substrate-induced sodium currents can put cells at risk, as (1)fenfluramine is associated with neuronal depletion of 5-HT , and amphetamine can indirectly activate voltage-gated Ca 21 channels (Cameron et al, 2015). The substrates identified here, especially those that had efficacies similar to METH, may cause depolarization in neurons, as evidenced by the dose-dependent currents elicited by 4-MEC in Xenopus oocytes expressing hSERT (Saha et al, 2015).…”
Section: Discussionmentioning
confidence: 80%